Removal of Direct Blue 71 and chromium from aqueous solutions by metal coating organic adsorbents, metal coating biochar and biochar-metal composite - Parichehre, Maedeh; Sadeghzadeh, Fardin; Jalili, Bahi; Bahmanyar, Mohammad Ali; Samsuri, Abd Wahid (University of Mohaghegh Ardabili, Water Management Research Center, 2023)
Widespread entry of effluents, which are toxic and non-biodegradable, from factories and various industries into the environment, and accordingly, pollution of water and soil resources lead to many dangers for humans and other organisms. Therefore, modification of these resources is important. Currently, multiple technologies from the physical, chemical, and biological perspectives have been established for the remediation of contaminated water. However, most of them involve energy consumption, high-cost instruments, low efficiency, complicated implementation, or secondary pollution. Therefore, it is critical to develop more convenient, economic, and environmentally harmonious strategies for the decontamination of polluted water. Biochar is an emerging material that is manufactured by the decomposition of carbon-rich biomass under oxygen-limited pyrolysis. Remarkable progress has been made in the understanding of biochar as an environmentally friendly and low-cost material for carbon sequestration, energy recovery, contamination relief, and nutrient supplementation. In recent decades, biochar has gained significant attention in the remediation of contamination in terrestrial and aquatic environments. However, biochar only has limited adsorption ability to anionic contaminants in water. This is because biochar often has a negative surface charge, hindering it to absorb negatively charged compounds such as Cr(VI) and Direct Blue71. Various modification methods thus have been developed to improve its affiliation to anionic contaminants by introducing metal oxides onto the carbon surface within its pore networks. Studies showed that the application of biochar and metal-coated biochar, effectively leads to the removal of significant amounts of contaminants from water and soil, but so far the impact of metal-carbon composite on the removal of contaminants, especially anionic contaminants has not been reviewed. Therefore, the purpose of this research is to produce different types of biochar-metal composites, to investigate the effectiveness of different types of composites in removing Direct Blue 71 and chromium from aqueous solution, and also to compare the composites with: plant biomass, metal-coated biomass, biochar, and metal coated biochar.